Some mitochondrial genes perform better for damselfly phylogenetics: species‐ and population‐level analyses of four complete mitogenomes of Euphaea sibling species. (11th April 2018) - Cheng, Yun‐Chieh; Chen, Ming‐Yu; Wang, Jo‐Fan; Liang, Ai‐Ping; Lin, Chung‐Ping
Abstract: Animal mitochondrial genes continue to provide an efficient and inexpensive assessment of genetic diversity. However, which mitochondrial genes should be selected to best estimate species phylogeny and population genealogy remains uncertain for most under‐sampled taxa. We analysed four complete mitochondrial genomes of sibling species of Euphaea damselflies, E. decorata, E. ornata, E. formosa and E . yayeyamana (Insecta, Odonata, Euphaeidae), to examine the patterns of selection and to evaluate the phylogenetic utility of the mitochondrial genes compared with nuclear genes. The results indicated that mitochondrial protein‐coding nad2 (NADH dehydrogenase subunit 2) and noncoding A + T‐rich (control region) genes have the highest mutation rates and more phylogenetic utility [higher parsimony‐informative sites; higher α (the shape parameter of gamma distribution); lower rates of heterogeneity among sites; and higher relative substitution rates] than all the other mitochondrial and nuclear genes analysed. In contrast, the animal DNA barcoding gene cytochrome c oxidase subunit 1 ( cox1 ) had average values for all estimated parameters of phylogenetic performance and was sometimes outperformed by other mitochondrial genes. The majority of the mitochondrial and nuclear genes in Euphaea damselflies have experienced frequent purifying selection, except for two cases of potential positive selection in NADH dehydrogenase subunit 3 ( nad3 ) and elongation factor 1 α ( EF1α ), and all mitochondrial genes had experienced stronger purifying selection than nuclear genes. Our findings indicated that mitochondrial nad2 and the A + T‐rich region should be selected to provide efficient and high‐resolution phylogenetic markers for damselflies at the species and population level. Abstract : We analysed four complete mitochondrial genomes of sibling Euphaea damselflies to examine the patterns of selection and to evaluate the phylogenetic utility of the mitochondrial genes compared with nuclear genes. The results indicated that mitochondrial protein‐coding NADH dehydrogenase subunit 2 ( nad2 ) and non‐coding A + T‐rich (control region) genes have more phylogenetic utility than all the other mitochondrial and nuclear genes analysed. Our findings suggested that mitochondrial nad2 and the A + T‐rich region should be selected to provide efficient and high‐resolution phylogenetic markers for damselflies at the species and population level.